2013
DOI: 10.4236/nr.2013.41007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of NaHCO<sub>3</sub> as Catalyst via Electrolysis

Abstract: Renewable energy is a kind of energy that comes from natural sources like water, sunlight, wind and so on. Water electrolysis is currently the most dominant technology used for hydrogen production from renewable sources because of high energy conversion efficiency. In this present work, the effect of NaHCO 3 via electrolysis was studied. Stainless steel is chosen to be as the electrode and different concentrations of NaHCO 3 are used as alkaline solutions in electrolysis system. The rates of hydrogen gas produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Jabar and Ibrahim explained that the rate of hydrogen produced using NaHCO 3 was higher than NaOH. They founded that the weight loss of electrodes in the samples of NaHCO 3 and NaOH is approximately similar to the weight loss of electrodes in the water sample under the same condition [45]. Abdel-Aal et al in 2010 showed the influence of changing the Cl -concentration in sea water on the ratio of hydrogen to total chlorine.…”
Section: Effect Of Electrolyte Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Jabar and Ibrahim explained that the rate of hydrogen produced using NaHCO 3 was higher than NaOH. They founded that the weight loss of electrodes in the samples of NaHCO 3 and NaOH is approximately similar to the weight loss of electrodes in the water sample under the same condition [45]. Abdel-Aal et al in 2010 showed the influence of changing the Cl -concentration in sea water on the ratio of hydrogen to total chlorine.…”
Section: Effect Of Electrolyte Concentrationmentioning
confidence: 99%
“…The different pH level can cause different type of gas to be produced. On the other hand, the weight loss of stainless steel, gas production and the pH value at 0.4 M of sodium bicarbonate and sodium hydroxide are good production [45].…”
Section: Effect Of Phmentioning
confidence: 99%